2015
DOI: 10.1111/jop.12382
|View full text |Cite
|
Sign up to set email alerts
|

E‐cadherin regulators are differentially expressed in the epithelium and stroma of keratocystic odontogenic tumors

Abstract: The high immunoexpression of Snail and nuclear Slug in keratocystic odontogenic tumors suggests these proteins as transcription factors without necessarily participating in 'cadherin switching'. However, the knowledge of their induction of the epithelial-mesenchymal transition in odontogenic tumors is still limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…When the left and right palatine processes fuse after contact, epithelial cells lose their polarity in the epithelial cord and either reconstruct their cytoskeleton to convert to mesenchymal cell traits, which is called the epithelial-mesenchymal transition (EMT), or undergo apoptosis [35][36][37][38][39][40]. In this study, E-cadherin-, β-catenin-, and α-catenin-positive cells were found in the midline epithelial cord of the anterior palate in the TCDD-treated group, and TUNEL-positive cells were found in the same area.…”
Section: Discussionmentioning
confidence: 99%
“…When the left and right palatine processes fuse after contact, epithelial cells lose their polarity in the epithelial cord and either reconstruct their cytoskeleton to convert to mesenchymal cell traits, which is called the epithelial-mesenchymal transition (EMT), or undergo apoptosis [35][36][37][38][39][40]. In this study, E-cadherin-, β-catenin-, and α-catenin-positive cells were found in the midline epithelial cord of the anterior palate in the TCDD-treated group, and TUNEL-positive cells were found in the same area.…”
Section: Discussionmentioning
confidence: 99%
“…Various EMT induced factors like inflammatory factors may change the balance between epithelial character maintenance and EMT. The disruption of this function may be involved in root morphology abnormalities and the development of odontogenic cysts and tumors originating from HERS and ERM 24 . In future, exhaustive single cell analysis about signaling associated with EMT is needed.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, the cell increases its ability to invade, migrate, and generate metastasis. The dissociation of tumor cells across tissues due to changes in cell-cell adhesion is one of the main causes of the tumor's invasive capacity [8], being a possible explanation for the aggressive behavior of OK.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of EMT in tumor metastasis formation is based on observations that epithelial carcinoma cells that acquired mesenchymal markers such as vimentin and loss of cell-cell adhesion molecules such as E-cadherin [9] were associated with a higher metastatic potential. Currently, the most commonly used markers for EMT verification are vimentin, fibronectin and N-cadherin (mesenchymal markers), E-cadherin (epithelial markers) and Snail and Slug (transcription factors) [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation